Positive Signals of Tax Incentives for Medium-sized Companies - Mar’atus Zahro; Ardilla Ayu Kirana; Kasrowi; Rika Rahayu (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to obtain empirical evidence of the effect of the Regulation of the Minister of Finance of the Republic of Indonesia Number 44/PMK.03/2020 concerning tax incentives for taxpayers affected by the corona virus pandemic on medium-sized companies. In addition, to obtain empirical evidence of the types of tax incentives that are most effective for medium-sized companies. This research uses descriptive qualitative methods by analyzing data as supporting data adjusted to field case studies. The results showed that: first, the most effective tax incentive program for medium-sized companies is the final income tax incentive PP No. 23 of 2018 borne by the Government because for small and medium companies this tax incentive can increase the company's cash inflow. Second, income tax article 21 incentives are not very effective because most employees have income below Non-Taxable Income. Third, the income tax article 25 reduction facility is only delaying so that the cash inflow received by the company during the utilization of this facility is only temporary. Fourth, tax exemption on dividends is a good signal for company managers and shareholders to immediately distribute dividends.